Effect of stretching-based rehabilitation on pain, flexibility and muscle strength in dancers with hamstring injury: A single-blind, prospective, randomized clinical trial - Kim, G.; kim, H.; Kim, W. K.; Kim, J. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Hamstring injuries commonly occur in mainstream sports and occupations that involve physical activity. We evaluated the effect of a stretching-based rehabilitation program on pain, flexibility, and strength in dancers with hamstring injuries. METHODS: Sixteen Korean traditional dancers with unilateral hamstring injuries were included and randomly assigned to a rehabilitation or control group. The rehabilitation group received stretching-based rehabilitation for 8 weeks, which comprised simple static stretches and basic range of motion (ROM) exercises, such as static and active stretching, concentric and eccentric ROM training, and trunk stabilization exercises. The control group received conventional treatment with analgesics and physical therapy. Outcomes were assessed before and after the interventions in both groups by comparing the Visual Analog Scale (VAS) score for pain, straight leg raise ROM Test for hamstring muscle flexibility, and isometric strength test for hamstring muscle strength. RESULTS: Subjects who underwent rehabilitation showed significant improvements in VAS score for pain (P=0.017) and ROM for flexibility (P<0.001). Muscle strength also increased after the rehabilitation program (P<0.05). CONCLUSIONS: This rehabilitation program effectively decreases pain and increases flexibility and strength in patients with hamstring injury. The data indicate that a stretching-based rehabilitation program can help promote functional recovery from hamstring injury.